Role of secretome mesenchymal stem cells as immunomodulator in periodontal diseases - Desi S. Sari; Ernie Maduratna; Candra Bumi; I-Ketut Sudiana; Fedik A. Rantam (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of this review literature is to look at the mechanism of mesenchymal stem cell secretome in the regeneration of periodontal tissue.Methods: This literature review was collected from several journals and research that has been done, where the application of Mesenchymal stem cells (MSCs) promises a favourable result for cell-based therapy in inflammatory diseases, immune system disorders, regeneration, and tissue repair.Results: MSCs possess a potent immunomodulatory function, paracrine effects, and the ability to differentiate into different cells. Not only mesenchymal stem cells can replace damaged tissue or cells but also secrete secretome namely bioactive ingredients such as cytokines, chemokines, growth factors, pro-inflammatory, and anti-inflammatory which play an essential role in regulating the host immune system. Periodontal disease is an inflammatory disease that occurs in the teeth supporting structures. Lately, many therapies for periodontal disease utilized MSCs from gingival tissue and periodontal ligaments. Secretome activates endogenous MSCs to improve the immune system in periodontal disease that might create a better microenvironment of periodontal tissue.Conclusion: The secretome of MSCs has attracted a lot of attention and has the potential to repair and regenerate tissues including periodontal tissue